Effect of surface treatment of wood on the fire resistance of wooden structures - Цапко, Юрий Владимирович (Eastern-European Journal of Enterprise Technologies, 2013)
Flame spread during burning up of materials determines the intensity and dynamics of fire, depending on the effectiveness of the protection and the burn-up rate of building structures in the burning flame. A mathematical model of the burn-up rate of woodis given. For obtaining analytical equation the burning rate of refractory material is calculated with the corresponding value of the indicator of slowing down, installations, the change of particular structure and properties of the contact zone of the wood. A layer of wood is characterized by resistance to external sources of energy (high flame), which suggests the protective nature of the wood surface modifiers. Stability of modified wood was estimated to change the compressive strength on the average 3 times higher compared with the untreated wood structure burn-up. Thus, the treatment of wood helps to reduce the burn-up rate and hence increases the resistance of structures.